Building effective partnerships in the Nile BDC—group feedback - Amede, Tilahun (International Livestock Research Institute, 2011)
In early May 2011, people working on the Nile Basin Development Challenge (http://nilebdc.org) met in Addis Ababa in a 'science and reflection workshop'. Session 2 of the workshop examined institutional and other processes that are key to success of the overall program. In this video, Tilahun Amede (ILRI) reports from small group discussions on issues of partnership in the Program: How do we streamline, integrate, and coordinate the engagement of the various NBDC projects with national research partners?